New Challenges for a Collaborative Urban Planning: Digital Platform for Promoting Relationship Between Local Administration and Citizens in the City of Malaga - Francisco Jose Chamizo Nieto; Nuria Nebot Gomez de Salazar; Carlos J. Rosa-Jimenez (ARCHive-SR, 2019)
The most conventional systems in the Urban Planning practice leave out needs and real social demands through inefficient management models in many cases. Nowadays there is a social, professional and institutional demand to transform these models into new ways of thinking and planning the city that are closer to its inhabitants. In fact, there is a high social involvement of people that are helping or developing activities in favour of their local communities. However, this social activism is not visible nor recognised as the one made by regulated associations. Undoubtedly, the use of new technologies offers a framework of opportunity in these new ways of ”making the city”, as well as it becomes a new area of work and research.